the Ameliorative effects of ascorbic acid on hematological and water quality parameters following a 100 km transportation of adult Clarias gariepinus - Adah, Deborah Arimie; Adah, Adakole Sylvanus; Nwonuma, Charlse Obiora; Olaosebikan , Boluwaji; Oyekunle , Taiwo (Universitas Airlangga, 2023)
Experiments were performed to determine the effects of ascorbic acid on haematological and water quality parameters of Clarias gariepinus subjected to road transportation. A total of 40 apparently healthy adult Clarias gariepinus of an average weight of 450.46 ± 23.06 g and an average length of 38. 23 ± 4.46 cm were used for the experiment and were divided into two groups. Group I (AAF) was administered ascorbic acid daily for one month and on the day of transportation while group II (NAF) was not administered. After transportation of the erythrocyte counts, packed cell volume was significantly higher in group I (P < 0.05). Total leucocyte count, neutrophil count, and neutrophil/lymphocyte ratio of group I were significantly lower (P < 0.05) in group I compared to group II. The concentrations of nitrite, nitrate, and ammonia were significantly higher (P < 0.05) in group II compared to group I post-transportation. The dissolved oxygen content of group I was however higher (P < 0.05) in group I compared to group II. It was therefore concluded that ascorbic acid modulated some haematological and water quality parameters of Clarias gariepinus and may be beneficial to the fish in ameliorating the stress of transportation.